How do healthcare providers manage depression in people with spinal cord injury? - Capron, Maclain (Spinal Cord Ser Cases, 2020)
STUDY DESIGN: An online survey. OBJECTIVES: To describe how healthcare providers manage depression after spinal cord damage (SCD) and to identify factors that predict use of recommended depression management practices. SETTING: An international cohort of respondents who provide clinical care to individuals with SCD. METHODS: An online survey was distributed to clinicians caring for individuals with SCD. The 20-question survey inquired about participant demographic and professional information, their knowledge and beliefs about depression after SCD, their methods of treating depression in SCD, and perceived barriers to treatment of depression. RESULTS: One hundred eleven individuals took this survey. Participants estimated on average that 48.7% of their patients with SCD have depression, and nearly two-thirds (62.2%) reported using their own clinical judgment to identify the condition. Respondents cited barriers to depression treatment including patient denial of depression (47.7%), stigmas attached to depression (41.4%), and lack of availability and high cost of counseling (45.9% and 35.1%, respectively) and antidepressant medications (5.4% and 10.8%, respectively). The belief that one is well trained to handle depressive symptoms predicted increased frequency of screening for depression and implementation of recommended treatments for depression. CONCLUSIONS: Respondents to this survey under-utilize valid screening measures and likely over-estimate the prevalence of depression in SCD. They cited a number of barriers to treatment for depression. Our results underscore the need for improved mental health education among SCD providers and the use of valid depression screening measures to help focus limited mental health services and treatments on those who need them.